Benchtop nuclear magnetic resonance based on Halbach arrays applied to agriculture: A literature review (Research, Society and Development, 2026)
Low-field Nuclear Magnetic Resonance (NMR) based on permanent magnets has emerged as a promising alternative to conventional high-field systems, especially for applications outside the laboratory environment. In this context, Halbach-type magnet arrays stand out for their ability to generate intense, homogeneous, and self-shielded magnetic fields in compact devices with low operating costs. The objective of this article is to critically review the state of the art of benchtop NMR based on Halbach arrays and its applications in the agricultural and agri-food sector. The methodology adopted consisted of a systematic review of the scientific literature published in recent decades, covering topics ranging from the physical fundamentals of low-field NMR, principles of relaxometry and Halbach magnet engineering, to advanced strategies for field homogenization, thermal stability, and signal processing. Relevant applications in phenotyping and in vivo plant physiology, soil water monitoring, seed and grain quality assessment, meat science, food quality control, and nutrient and biofuel monitoring are discussed. The analyzed studies demonstrate that Halbach-based NMR sensors enable rapid, non-destructive, and volumetric analyses directly in the field or in processing lines, overcoming limitations of surface optical methods. It is concluded that the integration of Halbach arrays with advanced signal processing techniques, chemometrics, and artificial intelligence represents a strategic path for the democratization of NMR and for the advancement of precision agriculture and agro-industrial quality control.